2013
DOI: 10.1111/pme.12303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eye Movement Desensitization and Reprocessing (EMDR) Treatment in Chronic Pain Patients: A Systematic Review

Abstract: Although the results of our study suggest that EMDR may be a safe and promising treatment option in chronic pain conditions, the small number of high-quality studies leads to insufficient evidence for definite treatment recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 26 publications
2
52
0
7
Order By: Relevance
“…Therefore, EMDR therapy is beneficial in the treatment of chronic pain and somatic symptoms. Consistent with accumulated evidence in the literature supporting the potent efficacy of EMDR in the treatment of somatic symptoms (Kleinstauber et al, 2011;Tefft & Jordan, 2016;Tesarz et al, 2014) the present results provided further support and extended the relevant findings. The reported scores of EMDR treated patients with SSD on the SF-36 improved considerably in all domains.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, EMDR therapy is beneficial in the treatment of chronic pain and somatic symptoms. Consistent with accumulated evidence in the literature supporting the potent efficacy of EMDR in the treatment of somatic symptoms (Kleinstauber et al, 2011;Tefft & Jordan, 2016;Tesarz et al, 2014) the present results provided further support and extended the relevant findings. The reported scores of EMDR treated patients with SSD on the SF-36 improved considerably in all domains.…”
Section: Discussionsupporting
confidence: 80%
“…Studies investigating the effect of EMDR on physical symptoms, mostly chronic pain, suggest that treatment aimed at processing unresolved trauma and somatic symptom-related memories can reduce the somatic symptom by reducing the affective dimension of these memories or by integrating the somatic memory components (Tesarz et al, 2014; Van Rood & De Roos, 2009). We suggest that this explanation could also account for the reduction in tinnitus distress after EMDR.…”
Section: Discussionmentioning
confidence: 99%
“…The therapists were supervised regularly (at least two times per patient) by an EMDRIA-approved consultant (Günter H. Seidler). Before starting the study, a treatment manual was developed to guarantee standardized treatment (30). Each therapist underwent 3-day training on the manual.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, preliminary studies (case reports and case series) have used EMDR to treat chronic pain and have indicated that EMDR is able to clinically significantly reduce pain intensity and disability in patients with various pain disorders (27). Furthermore, EMDR improves pain-coping abilities and facilitates relaxation, which reduces pain and pain-related attitudes and beliefs (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation